Infeksi Cryptosporidium pada Manusia: Patogenesis, Diagnosis dan Terapi - Hatimi, Fahmi Ilham; Mutiara, Hanna; Islami, Suryadi; Sukohar, Asep (Medula, 2025)
Cryptosporidium is a zoonotic protozoan parasite capable of infecting humans and animals, primarily transmitted through contaminated water or food. This infection is a leading cause of moderate to severe diarrhea, particularly in children from low-income regions and immunocompromised individuals, contributing to significant global morbidity and mortality. The pathogenesis of Cryptosporidium involves the invasion of intestinal epithelial cells, resulting in mucosal damage, villous atrophy, and increased intestinal permeability, leading to watery diarrhea. Local inflammatory responses exacerbate symptoms, while immunocompromised individuals often experience chronic infections with serious complications. Diagnosis relies on microscopy, immunofluorescence, and molecular techniques such as PCR, which offer high sensitivity and specificity. Supportive care is the mainstay of treatment, with nitazoxanide being the preferred therapeutic option for selected patients. For immunocompromised individuals, management is more complex and may involve immune restoration therapies, such as antiretroviral treatment for HIV/AIDS patients. However, resistance to conventional treatments remains a significant challenge, necessitating further research into novel therapeutic agents, such as KDU731, which has shown promising efficacy in preliminary studies. This review provides a comprehensive analysis of the pathogenesis, diagnostic methods, and therapeutic strategies for Cryptosporidium infections. Additionally, it highlights the importance of prevention measures, including improved access to clean water and public health education. Enhanced control efforts are crucial to mitigating the global health impact of this infection, particularly among vulnerable populations such as children and immunocompromised individuals.